The role of domestic reservoirs in domestically acquired Salmonella infections in Norway: epidemiology of salmonellosis, 2000–2015, and results of a national prospective case–control study, 2010–2012. (15th November 2018) - MacDonald, E.; White, R.; Mexia, R.; Bruun, T.; Kapperud, G.; Brandal, L. T.; Lange, H.; Nygård, K.; Vold, L.
Abstract: In Norway, incidence of sporadic domestically acquired salmonellosis is low, and most frequently due to Salmonalla Typhimurium. We investigated the risk factors for sporadic Salmonella infections in Norway to improve control and prevention measures. Surveillance data for all Salmonella infections from 2000 to 2015 were analysed for seasonality and proportion associated with domestic reservoirs, hedgehogs and wild birds. A prospective case–control study was conducted from 2010 to 2012 by recruiting cases from the Norwegian Surveillance System for Communicable Diseases and controls from the Norwegian Population Registry (389 cases and 1500 controls). Univariable analyses using logistic regression were conducted and a multivariable model was developed using regularised/penalised logistic regression. In univariable analysis, eating snow, dirt, sand or playing in a sandbox (aOR 4.14; CI 2.15–7.97) was associated with salmonellosis. This was also the only exposure significantly associated with illness in the multivariable model. Since 2004, 34.2% ( n = 354) of S. Typhimuirum cases had an MLVA profile linked to a domestic reservoir. A seasonal trend with a peak in August for all Salmonella types and in February for S. Typhimurium was observed. Indirect exposure to domestic reservoirs remains a source of salmonellosis in Norway, particularly for children. Information to the public about avoiding environmental exposure should be strengthened and initiatives to combat salmonellosis in the food chain should be reinforced.